LINKING BEHAVIOR THEORY AND FAITH-BASED MANAGEMENT: IMPLEMENTING TPB IN ISLAMIC DECISION CONTEXTS - Mustara, Eha Nugraha (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2025)
This study presents a systematic literature review of fifteen scholarly articles examining the implementation and implications of the Theory of Planned Behavior (TPB). The reviewed literature is categorized into two main groups: (1) bibliometric and metadata-based studies and (2) empirical studies focusing on the application of TPB in the context of sharia accounting, particularly within zakat management entities. Relevant articles were sourced from Google Scholar from 2017 to 2024 and analyzed using SciSpace AI software (Typeset.io). To strengthen the bibliometric dimension, a bibliometric graph is included to illustrate the distribution of research methods, publication trends, and thematic focus. The results indicate that behavioral finance research predominantly employs empirical and archival methods, while behavioral accounting tends to rely on experimental approaches. Furthermore, the review shows that Muzakki compliance behavior can be predicted through attitudes, subjective norms, and perceived behavioral control, aligning with the core constructs of TPB. This article contributes to the theoretical and practical understanding of zakat compliance behavior and offers a foundation for developing effective strategies and policies to enhance the performance of zakat institutions.